Meaningful changes for efficacy outcomes in patients with chronic rhinosinusitis with nasal polyps - Jessica Braid, MS; Lutaf Islam, DVM; Cristian Gugiu, PhD; Theodore A. Omachi, MD; Helen Doll, BSc (World Allergy Organization Journal, 2023)
Objective: Nasal Polyp Score (NPS) and Nasal Congestion Score (NCS) are commonly used clinical trial endpoints to determine improvements in response to treatment in patients with chronic rhinosinusitis with nasal polyps (CRSwNP). However, limited information is available on within-patient meaningful change thresholds (MCTs) and between-group minimal important differences (MIDs) for NPS and NCS, which would aid interpretation of results. Methods: Data from phase 3 placebo-controlled trials of omalizumab in patients with CRSwNP (POLYP 1 and POLYP 2) were used to estimate MCTs and MIDs for both NPS and NCS using anchor-based methods. Sino-Nasal Outcome Test-22 (SNOT-22) and SNOT-22 Sino-Nasal Symptoms Subscale (SNSS) scores were used as anchors (≥0.35 correlation with NPS and NCS). Within- and between-group differences in NPS and NCS change scores were used to estimate MCTs and MIDs, respectively. Identified MCTs were used in unblinded responder analyses to compare the proportions of patients per treatment group achieving a meaningful improvement. Results: MCTs and MIDs were estimated at −1.0 and −0.5 for NPS and −0.50 and −0.35 for NCS, respectively, and were consistent across studies. Overall, 57.0% of patients achieved the MCT in NPS with omalizumab vs 29.9% with placebo (p < 0.0001). Similarly, 58.9% of patients achieved the MCT in NCS with omalizumab vs 30.7% with placebo (p < 0.0001). Group differences in mean change were statistically significant and exceeded the estimated MIDs. Conclusions: Meaningful change estimates for NPS and NCS could be used to assess response to treatment for patients with chronic rhinosinusitis with nasal polyps.Trial registration: POLYP1: clinicaltrails.gov NCT03280550; registered September 12, 2017; https://clinicaltrials.gov/ct2/show/NCT03280550). POLYP2 (clinicaltrials.gov NCT03280537; registered September 12, 2017; https://clinicaltrials.gov/ct2/show/NCT03280537).